KOMPETENSI INTERNASIONAL AKUNTANSI FORENSIK MAHASISWA AKUNTANSI DI BEBERAPA UNIVERSITAS DI SEMARANG - Rizky Garuda Nusantara Bachrul Zakir Hamzah, Muhammad; Yanto, Heri (Jurnal Riset Akuntansi dan Keuangan, 2015)
In the era of globalization accounting graduates equipped with international competencies would have better access to find jobs in other countries. The roles of universities in preparing their accounting graduates are pivotal. The objectives of the study is to identify the contributions of univesities in preparing their graduates to master international competencies of forensic accounting (KIAF). The population of the study are final-year accounting students of all universities in Semarang. By employing multi-stage smpling technique, the study collected 218 data. Moreover, the study used a five-point-Likert-type scale for both variables of accounting course enggagement (KMPA) and KIAF. KMPA was the proxy for measuring the process of accounting education at the university.Descriptive, correlation, and regression analyses were employed to analyze data. Almost all factors of KMPA significantly correlate with factors of KIAF. Canonical analysis shows that covariates of KMPA factors mostly correlate with canonical variable. Almost all factors of KMPA have significant contributions in building students’ competencies of forensic accounting Universities should improve the education processes of accounting to increase the KIAF. Since, the KIAF was measured using students’ perceptions, future research should focus on the impacts of KMPA on real competency of forensic accounting.